The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0037-86821997000100013
|View full text |Cite
|
Sign up to set email alerts
|

Entomoftoromicose intestinal: relato de caso

Abstract: RELATO DE CASOPaciente de 19 anos, agricultor, natural e procedente de Araguaiana (Mato Grosso, Brasil), admitido no hospital com história de massa abdominal, evoluindo há 3 meses, associada à febre, sudorese, diarréia e perda de 9kg no período. O paciente tinha antecedentes alimentares de ingestão de pães mofados.Ao exame físico, estava em regular estado geral e à palpação do abdome havia uma tumoração na fossa ilíaca direita, de 4 por 6cm, endurecida, dolorosa e pouco móvel. Os achados laboratoriais revelara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Eight of these 19 patients had been described separately before being finally reviewed by Vikram et al, in 2012 together with other 25 cases observed outside the United States [21]. All the detailed published cases (with the exception of 12 cases reported in the review by Vikram and not singularly described) plus the one observed by us are summarised in Table 2 [4,12,[14][15][16][17][18][19][20]. We noted that a further 18 pediatric cases of basidiobolomycosis were reported in 2017 but they are not included in the present review because of the lack of any detailed information regarding single cases [63].…”
Section: Review Of the Literaturementioning
confidence: 89%
See 3 more Smart Citations
“…Eight of these 19 patients had been described separately before being finally reviewed by Vikram et al, in 2012 together with other 25 cases observed outside the United States [21]. All the detailed published cases (with the exception of 12 cases reported in the review by Vikram and not singularly described) plus the one observed by us are summarised in Table 2 [4,12,[14][15][16][17][18][19][20]. We noted that a further 18 pediatric cases of basidiobolomycosis were reported in 2017 but they are not included in the present review because of the lack of any detailed information regarding single cases [63].…”
Section: Review Of the Literaturementioning
confidence: 89%
“…Although a definite diagnosis can be obtained with culture [14,15,18,19,[22][23][24]30,33,35,41,45,47,[49][50][51]54,59,62], it was frequently missed in previous reports because of the lack of suspicion that made tissue specimens unavailable for culture purpose. Therefore, the diagnosis of gastrointestinal infection by B. ranarum was mainly obtained on histologic examination, which typical morphologic features include granulomatous inflammation and a diffuse eosinophilic infiltrate with thin walled branched hyphae surrounded by eosinophilic material (Splendore-Höeppli phenomenon) and sometimes zygospores (spherical bodies with foamy cytoplasm) [4,6,12,16,17,20,24,[26][27][28][29][31][32][33][35][36][37][38][39][42][43][44]46,49,52,53,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most cases of conidiobolomycosis are reported from the African continent, mainly Nigeria. 36 There is a 10 : 1 male/female ratio, and the disease occurs predominantly in young adults. 1,2 Conidiobolus is transmitted by inhalation of fungal spores, which then invade the nasal tissue, the paranasal sinuses and facial soft tissues.…”
Section: Conidiobolomycosismentioning
confidence: 99%